2019
DOI: 10.3390/cancers11111685
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Patient Heterogeneity of Circulating Tumor Cells and Circulating Tumor DNA in Blood of Melanoma Patients

Abstract: Despite remarkable progress in melanoma therapy, the exceptional heterogeneity of the disease has prevented the development of reliable companion biomarkers for the prediction or monitoring of therapy responses. Here, we show that difficulties in detecting blood-based markers, like circulating tumor cells (CTC), might arise from the translation of the mutational heterogeneity of melanoma cells towards their surface marker expression. We provide a unique method, which enables the molecular characterization of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 47 publications
1
30
0
3
Order By: Relevance
“…The CTC detection frequency in this study was, however, lower than in most previously published papers on MM patients (Aya‐Bonilla et al , 2017; Koyanagi et al , 2010; Luo et al , 2014; Mocellin et al , 2004). We have recently shown that by using a combined a marker‐dependent (CSPG4 and CD146MACS microbeads) and marker‐independent (Parsortix, Angle plc) detection method, 32% of patients were CTC‐positive with an increase in CTC‐positivity with increased tumor staging (Gorges et al , 2019). However, due to the long processing time of this approach, in this study we decided to test a faster approach enabling the establishment of a clinically relevant multi‐analyte liquid biopsy assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CTC detection frequency in this study was, however, lower than in most previously published papers on MM patients (Aya‐Bonilla et al , 2017; Koyanagi et al , 2010; Luo et al , 2014; Mocellin et al , 2004). We have recently shown that by using a combined a marker‐dependent (CSPG4 and CD146MACS microbeads) and marker‐independent (Parsortix, Angle plc) detection method, 32% of patients were CTC‐positive with an increase in CTC‐positivity with increased tumor staging (Gorges et al , 2019). However, due to the long processing time of this approach, in this study we decided to test a faster approach enabling the establishment of a clinically relevant multi‐analyte liquid biopsy assay.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that a combination of different markers has shown to lead to a higher number of detected CTCs than the use of a single marker (Freeman et al , 2012; Po et al , 2019), the combination of four markers (MCAM, NG2, MART‐1, and HMB45) did not lead to an increase in CTC detection compared to only MCAM and NG2 in our study. Interestingly, there is also evidence that the markers on CTCs do not always correlate with the markers expressed on the primary tumor, which leads to the conclusion that CTCs could derive from a rare subpopulation of tumor cells (Aya‐Bonilla et al , 2019; Gorges et al , 2019; Gray et al , 2015), making the choice of right detection marker even harder. Therefore, due to the obviously large heterogeneity of melanoma CTCs and their marker expression, it is important to establish unbiased and marker‐independent detection methods and to focus on physical qualities such as cell size, morphology, and/or rigidity (Marsavela et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous assays for the direct detection of CTCs have been developed that allow for the analysis of CTCs at the single-cell stage in the peripheral blood. In a study of 84 patients with malignant melanoma, a combined analysis of ctDNA and CTCs predicted relapse earlier than imaging and was more accurate than serum LDH or S100 in a subset of patients [37]. Overall, 32% of patients were CTC-positive.…”
Section: Tumor Mutation Burden and Liquid Biopsies: Helpful For Treatmentioning
confidence: 94%
“…This standardization of novel technologies and workflows is much needed to increase the acceptance of CTCs as biomarkers in the clinic. The Parsortix ® system (ANGLE plc)-a size-based enrichment device -has been introduced to the CTC field and shown promising results across multiple tumor entities [19][20][21][22][23][24]. In addition to enumeration, the device has demonstrated its capabilities in isolating rare CTC clusters [24,25] and preserving cell viability following CTC enrichment [19,26].…”
Section: Introductionmentioning
confidence: 99%